Pengembangan Sistem Informasi Pembelajaran Daring Blended System berbasis Web - Asti Annisa Amalia; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The rapid development of technology also affects the world of education. Educational institutions have an important role in shaping the character of students and making students not blind to technology that is developing very rapidly. However, during this pandemic, educational institutions must stop the face-to-face learning process to stop the spread of this virus. Educational institutions must change the conventional learning system to become modern because it does not require a face-to-face process between teachers and students or what is commonly referred to as blended learning. PT. Lambda Solusi Informatika is a software house and wants to create a system to help solve this online learning process problem. The features in this system are adding courses, adding classes, adding instructors, applying courses, completing modules, completing tasks, and taking quizzes. This information system was developed using the waterfall method. In the need analysis stage, there were 73 functional requirements and 2 non-functional requirements. At the system implementation stage, the database used is MongoDB, and for the interface the author uses ReactJS. In system testing, a verification process for functional requirements is carried out using the white box method and the validation process for functional requirements using the black box equivalence partitioning method and manually testing non-functional requirements. With the construction of this system, it is hoped that it can simplify the learning process and be able to solve existing problems and hopefully it will be useful for users who will use this system.